FIRST RESULTS OF FISSION-TRACK THERMOCHRONOLOGY IN THE ALBANIDES - Muceku B.; Mascle G.H.; Tashko A. (My University, 2006)
Albania, situated at the boundary between the Dinaric and the Hellenic branchs of the Dinaro-Hellenic fold belt, has experienced a multiphase geodynamic evolution. The internal zones show a Mid-Jurassic episode of deformation characterized by ophiolite obduction, followed by development of a fold-and-thrust belt in the external zones during the Cenozoic. More recently, Albania has experienced a tensional regime. We present apatite and zircon fission-track (AFT and ZFT) measurements for 22 samples, and seven measurements of track-length distributions to elucidate the thermal evolution. AFT ages vary from 10.8 ± 0.7 Ma to 50.5 ± 5.7 Ma. The oldest ages (Eocene) occur in the western Albanides, corresponding to Eocene emplacement of the internal zones over the external ones. Neogene ages in the eastern Albanides suggest rapid exhumation, which we relate to an extensional regime. The ZFT ages show that the internal Albanides did not reach temperatures > 200 °C during the Cenozoic. © The Geological Society of London 2006.
Keywords: Neogene; Jurassic; Eocene; Cenozoic::Neogene; Кайнозой::Неоген; Mesozoic::Jurassic; Мезозой::Юрская; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен